SPECIMEN OF TACHYSURUS PLATYSOMUS WITHOUT PELVIC FINS - Menon, N Gopinatha (Indian Journal of Fisheries, 2011)
A single specimen of Tachysurus platysomus, from the trawl net catches from the Gulf of Mannar, without pelvic fins is described with reference to similar findings dsewfaere. There are many instances of the total absence cA the paired and uopaiied fiiÂ» among fishes (Dawson, 1964). But there are only few records of almormalities among siluroid fishes.